2018
DOI: 10.1177/0269215518757291
|View full text |Cite
|
Sign up to set email alerts
|

Early self-managed focal sensorimotor rehabilitative training enhances functional mobility and sensorimotor function in patients following total knee replacement: a controlled clinical trial

Abstract: Overall, the magnitude of improvements in functional mobility and sensorimotor function endorses using focal sensorimotor training as an effective mode of rehabilitation following knee replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…Pain and surgery lead to a temporary loss of motor function and muscle strength, which often seems to improve in the post-operative phase, especially following a rehabilitation regimen [9][10][11][12][13][14]. When patients exhibit pain or other post-surgical complications, their rehabilitation may be compromised and result in impaired function, loss of muscle strength and poor postural control.…”
Section: Introductionmentioning
confidence: 99%
“…Pain and surgery lead to a temporary loss of motor function and muscle strength, which often seems to improve in the post-operative phase, especially following a rehabilitation regimen [9][10][11][12][13][14]. When patients exhibit pain or other post-surgical complications, their rehabilitation may be compromised and result in impaired function, loss of muscle strength and poor postural control.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Incomplete proprioceptive recovery of the knee joint, poor mobility and unstable dynamic balance are factors that increase the risk of falls in the elderly, and are also common factors that lead to difficulty in completing daily activities. [13,14] It has been reported that 25% of patients will fall within 2 years after total hip or total knee arthroplasty, [15] resulting in physical and psychological trauma and a high cost to the patient. [16] Therefore, limb balance is particularly important for the basic daily activities and safety of patients with total knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete proprioceptive recovery of the knee, poor mobility and unstable dynamic balance are factors that increase the risk of falls in the elderly, and are also common factors that lead to di culty in completing daily activities. [13,14] It has been reported that 25% of patients will fall within 2 years after total joint arthroplasty, [15] resulting in physical and psychological trauma and a high cost to the patient. [16] Therefore, balance is particularly important for the basic daily activities and safety of patients with TKA.…”
Section: Introductionmentioning
confidence: 99%